MATERI PENDIDIKAN AKIDAH: STUDI ATAS PEMIKIRAN SYAIKH ABDURRAHMAN SIDDIK DALAM KITAB TAZKIRATUN LI NAFSI WA LI QOSSIRIINA MISSILII - Taufik Taufik (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2010)
Syaikh Abdurrahman Sidik has a deeply thought on akidah or faith. In the context of Islamic religious education at school or madrasah, the thought of Syaikh can be considered as a material to enrich Islamic religious learning. This article will elaborate five of thoughts of Syaikh about faith. It is considered as important thing in reserving ummah faith in daily live. This article will elaborate some of Syaikh’s thought, such as the matter of kalimah syahadat; fear and hope; obeyed and disobeyed, ni’mah and bala’; position af reason; and work and ‘ilm.